Narratives of change: how climate change narratives have evolved since the 1970s - Zarina Kulaeva (International Journal of Climate Change Strategies and Management)
Purpose – The purpose of this paper is twofold. First, we map the emerging climate narratives from the 1970s. Second, we examine how these narratives have shaped climate governance in addressing the consequences of climate change. Our analysis is based on a set of 12 interviews with climate change experts from various fields, including climate science, environmental policy, and environmental sustainability. The theoretical framework primarily draws from narrative analysis (Bruner, 1991; Riessman, 2005; Freeman, 2015), with a specific emphasis on its application within climate change studies (Bottici, 2010; Bushell et al., 2015; Fløttum and Gjerstad, 2017). Design/methodology/approach – The period of analysis starts from the 1970s. A period marked by growing concern and the creation of national and global organizations to address the effects of climate change. Semistructured interviews were conducted with a sample of 12 experts in the field using narrative analysis. We adopted an inductive approach, allowing climate narratives to emerge organically from the interview data, and facilitating the emergence of new topics and perspectives. Findings – Through interviews with climate experts, this study identifies three key narratives and critical shortcomings related to climate governance. The dominant climate narratives identified are apocalyptic environmentalism, greening capitalism and degrowth. Notably, greening capitalism and degrowth emerge as a dichotomous framework for understanding and interpreting climate change. By exploring these climate narratives, we highlight five critical shortcomings related to climate governance: increasing citizen participation through a bottom-up governance model, reforming the environmental subsidy framework, strengthening the science-policy interface, decoupling economic growth from energy dependence and developing innovative technological models beyond traditional green growth approaches. As a result, climate governance remains confined to these binary frameworks, and the challenges that were promised to be addressed decades ago largely remain unresolved. Originality/value – The value of this study lies in the fact that, on the one hand, it uses narrative analysis to investigate climate governance, and on the other hand, it does so through interviews with different actors. All this facilitates a holistic approach, and from a 50-year historical perspective, this study traces an evolutionary line of narratives and identifies the critical points of climate governance.